Republic of Turkey : Towards Improving the Service Quality of Electricity Distribution Companies - Energy Sector Management Assistance Program (World Bank, Washington, DC, 2017)
The objective of this review is to analyze the current status on achievement of targeted benefits from distribution privatization and identify the gaps between expectations and realizations, with a key task of proposing concrete procedures and methodologies to ensure that EMRA and other government agencies involved in monitoring and enforcing quality in electricity distribution and retail have timely access to reliable information on service actually provided by the DISCOMs to their customers. To reach these objectives, this report follows the following approach: section one presents an overview of the distribution sector and distribution privatization process; section two analyzes the existing regulatory framework related to DISCOM performance and provides expected performance targets in respective investment periods; section three analyzes the current status of DISCOMs’ performance targets; section four identifies key issues and barriers in measuring and monitoring service quality in DISCOMs; and lastly, based on the global experience, section five recommends an approach for improving measuring and monitoring of service quality by the regulator.